Multiobjective analysis of supply chain performance in terms of inventory, cost and service level - Bai, Wanying (2019)
Due to rapid globalization process, distribution channels of products have been enlarged to global scale and become more complicated. Therefore, manufacturing companies has been paying more attention to delivery and inventory control in recent decades. Reducing cost and maintaining high service level could help companies gain more benefit in the market. But cost, service level and inventory conflicts with each other in nature.